The Particularities of the Cost Calculation Method on Commands in Furniture Industry - Sabou, Felicia (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
The paper present the importance of the method on commands in cost calculation and the particularities of the cost calculation method on commands in the furniture industry. This paper presents a hypotetical study on the method on commands, considering the observations made during 2013-2014, on how it is organized and managed accounts management using method on commands.By presenting this hypothetical model about the accounting in management accounting using the method on commands, the paper contributes to the correct application of this method in practice, specifically in management accounting in companies from the furniture industry. In my opinion the method on commands is an appropriate method for achieving management accounting for companies that have as main activity the production of furniture. When applying the method on commands in cost calculation and in management accounting, the companies must to consider the particularities of the cost calculation, in the furniture industry, like: technical and economic factors from this sector, the technical details of each command, the codification of the commands, planning materials and labor costs for each command, monitoring and recording production costs, registration of the direct costs, distribution of the indirect costs on commands, registration of the indirect costs and registration in management accounting.